1999
DOI: 10.1175/1520-0434(1999)014<0625:dantvs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Descending and Nondescending Tornadic Vortex Signatures Detected by WSR-88Ds

Abstract: Tornadic vortex signatures (TVSs) of 52 tornadoes were identified and analyzed, then characterized as either descending or nondescending. This characterization refers to a known tendency of radar-observed tornadic vortices, namely, that of their initial detection aloft and then of their subsequent descent leading to tornadogenesis. Only 52% of the sampled TVSs descended according to this archetypal model. The remaining 48% were detected first near the ground and grew upward or appeared nearly simultaneously ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Our results, also obtained in a non-idealized modelling setting, extend the prevalence of this phenomenon to the regime of strongly forced systems in weakly unstable environments in the 'maritime' environment of the United Kingdom. Trapp et al (1999), McAvoy et al (2000) and Lane and Moore (2006) have drawn attention to the challenges posed to operational meteorologists by tornadoes and straight-line winds along QLCSs and NCFRs. Forecasting and nowcasting of such phenomena is a test of the limits of current modelling and operational radar capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, also obtained in a non-idealized modelling setting, extend the prevalence of this phenomenon to the regime of strongly forced systems in weakly unstable environments in the 'maritime' environment of the United Kingdom. Trapp et al (1999), McAvoy et al (2000) and Lane and Moore (2006) have drawn attention to the challenges posed to operational meteorologists by tornadoes and straight-line winds along QLCSs and NCFRs. Forecasting and nowcasting of such phenomena is a test of the limits of current modelling and operational radar capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Of greater interest is the descending nature of the cyclonic rotation that the PAR captures. The potential capability to diagnose the evolution of these velocity signatures may be particularly advantageous in studies of storms exhibiting nondescending vortex development such as those described in Trapp et al (1999).…”
Section: ) Analysismentioning
confidence: 99%
“…Other studies have shown some impact of storm type on tornado warning lead time. Trapp et al (1999) found tornadoes resulting from nondescending vortices, often associated with quasi-linear convective systems, were associated with shorter warning lead times. Guillot et al (2008) found higher tornado warning lead times for isolated supercells and strong convective lines but less lead time for weaker, less-organized systems.…”
Section: Discussionmentioning
confidence: 99%